Inter-relationship Between Body Measurements and Prices of Sheep in An Open Market in Kano State - Iyiola-Tunji, AO; Olugbemi, TS; Ali, AO; Ojo, AO (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
This study attempted to determine the inter-relationship between market price and body measurements among different breeds of sheep in open markets of six Local Government Areas of Kano State (Municipal, Taruauni, Gmale, Nassarawa, Fagge and Dala) of Kano city. Body measurements and prices of sheep used for this study were obtained from Unguwa Uku, Dorayi, Kara, Bachirawa, yankaba, Mariri and Kabara livestock markets in Kano. The Sudanese price was the highest (N 30,000±0.0), followed by Uda, Balami and Yankasa with the least cost being N 10, 614±3,137. Similarly the Sudanese breed recorded highest body weight, back length, lion girth and height at wither compared to all other breeds, while Balami had a higher chest girth (78.77±6.0 cm), followed by Uda and Yankasa, which recorded the least. The extra large animals weighed 58.75± 1.25 kg, which was more than the body weight of the large, medium and small sheep which weighed 42.48±0.34kg, 34.93±0.21 and 27.92±0.26, respectively. The price of these animals also follow the same pattern as the extra large cost more than all the other weight classes. The prices were N 25,750±8,500, N 15,524±2,263, N 11,284±2792 and N 8,324±1,584 for extra large, large, medium and the small sheep, respectively. Price of sheep was positive and highly correlated to weight of the sheep (0.826). Price was also positive and moderately correlated to back length (0.579), chest girth (0.538), height at wither (0.535) and leg length (0.464) at 1% level of significance. Leg length was highly and positively correlated with height at wither (0.717). Height at whither together with back length are important additional variables to chest girth to obtain up to 38% prediction of price of rams. The price of any sheep breed is subjected to the weight and the price of sheep in an open market can best be predicted from a combination of leg length and loin girth. (Animal Production 13 (1):64-68 (2011)Key Words: price of sheep, sheep breeds and open markets